Can Your Network Make You Happy? Entrepreneurs' Business Network Utilization and Subjective Well‐being. (26th December 2017) - Newman, Alexander; Mole, Kevin F.; Ucbasaran, Deniz; Subramanian, Nachiappan; Lockett, Andy
Abstract: We draw on the conservation of resources theory to examine whether self‐efficacy and resilience mediate the relationship between entrepreneurs' business network utilization and their subjective well‐being. Using socioemotional selectivity theory, we then examine the extent to which the mediating effects become stronger as entrepreneurs age. An analysis of data collected from 335 entrepreneurs in India reveals that business networks help entrepreneurs build resilience and self‐efficacy, which contribute to subjective well‐being. Furthermore, we find that the relationship between business network utilization and subjective well‐being strengthens as entrepreneurs age. Our findings attest to the importance of understanding how contextual resources in entrepreneurs' work environments influence their subjective well‐being by enhancing their personal psychological resources.